A low-defect and Na-enriched Prussian blue lattice with ultralong cycle life for sodium-ion battery cathode. (1st February 2020) - Yan, Changxiu; Zhao, Along; Zhong, Faping; Feng, Xiangming; Chen, Weihua; Qian, Jiangfeng; Ai, Xinping; Yang, Hanxi; Cao, Yuliang
Abstract: Prussian blue compounds have been considered as attractive candidate cathodes for sodium ion battery (SIB) due to open channel structure, tunable chemical compositions and potential high capacity. However, their low capacity utilization and insufficient cyclability have hindered their large-scale applications. In this work, a series of Na-enrich PB lattices (Nax Fe[Fe(CN)6 ]1-y · zH2 O) with different contents of [Fe(CN)6 ] vacancies and coordinated water are synthesized to investigate the effects of the lattice defects on the reversible capacities and cycling stabilities of the PB materials. It is found that decreasing the content of structural defects can greatly elevate the electrochemical performance of the PB cathodes. The as prepared low-defect and Na + -enriched Na1.81 Fe[Fe(CN)6 ]0.83 · 2.04H2 O lattice can achieve a high reversible capacity of >140 mAh g −1, a superior rate capability with 55.2% of its initial capacity at 10 C and a long-term cyclability with 78% capacity retention over 3700 cycles, possibly serving as a low cost, high capacity and cycle-stable cathode for Na ion batteries. Graphical abstract: Image 1 Highlights: A low-defect and Na-riched prussian blue (PB) is synthesized. The as prepared Na-riched PB has a monoclinic structure ( P2 1 /n ). The as prepared Na-riched PB exhibits high reversible capacity and long-term cyclability.